2014
DOI: 10.1111/more.12027
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Leadership, Traditionality, and Interactional Justice in the Chinese Context. 真实型领导力、传统性与交互公平感在中国环境中的关系

Abstract: We examine the effects of authentic leadership on subordinates in the Chinese context. Drawing on attribution processes of self-disclosure, we propose that authentic leaders engaging in self-disclosure practices cultivate subordinates' positive feelings that their leaders like and trust them. We further explain how and why authentic leadership particularly influences highly traditional Chinese subordinates. We propose that Chinese traditionality strengthens the positive effects of authentic leadership on subor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 73 publications
7
63
0
Order By: Relevance
“…At the same time, they found that the other three dimensions of Big-Five personalities, extraversion, conscientiousness and openness, were not significantly correlated with the perception of interactional justice. In the aspect of leader behaviors, Li and other scholars [18] reported that authentic leaders inclined to show more self-disclosure practices which could make their subordinate feel that they were liked and trusted by their leaders. As a result, the subordinate's perceptions of interactional justice would increase.…”
Section: The Influence Of Leader Factors On Perception Of Interactionmentioning
confidence: 99%
“…At the same time, they found that the other three dimensions of Big-Five personalities, extraversion, conscientiousness and openness, were not significantly correlated with the perception of interactional justice. In the aspect of leader behaviors, Li and other scholars [18] reported that authentic leaders inclined to show more self-disclosure practices which could make their subordinate feel that they were liked and trusted by their leaders. As a result, the subordinate's perceptions of interactional justice would increase.…”
Section: The Influence Of Leader Factors On Perception Of Interactionmentioning
confidence: 99%
“…Servant leadership meta-analysis 41 Bambale, Shamsudin, and Subramaniam (2015) Jaramillo et al (2009) Siddiqi (2013) Bavik, Bavik, and Tang (2017) Johnson (2016) Trivers (2009) Bobbio, van Dierendonck, and Manganelli (2012) Liden et al (2015) Tuan (2017) Bouzari and Karatepe (2017) Liden et al (2008) van Dierendonck andNuijten (2011) Brubaker, Bocarnea, Patterson, and Malingumu, Stouten, Euwema, and Babyegeya (2016) Vondey (2010) Chen et al Gilmore, Hu, Wei, Tetrick, and Zaccaro (2013) Li, Yu, Yang, Qi, andFu (2014) Gong, Huang, andFarh (2009) LMX -Creativity Aleksi c, Miheli c, Cerne, and Skerlavaj (2017) Liao, Liu, and Loi (2010) Pan, Wu, Zhou, and Lou (2015) Chughtai (2016) Martinaityte and Sacramento (2013) Tierney, Farmer, and Graen (1999) Huang, Krasikova, and Liu (2016) Meng, Tan, and Li (2017) van Dyne, Jehn, and Cummings (2002) Jiang and Yang (2015) Muñoz-Doyague and Nieto (2012) Volmer, Spurk, and Niessen (2012) Joo ( …”
Section: Continuedmentioning
confidence: 99%
“…Specifically, when subordinates are shown empathic concern for their needs and openness to their opinions by their leaders, they are more likely to feel valued and respected, which increases their sense of interpersonal justice (Schuh et al, 2017). Accordingly, studies have found a positive relationship between followers' justice perceptions and both authentic leadership (Kiersch & Byrne, 2015;Li, Yu, Yang, Qi, & Fu, 2014) and leaders' trait mindfulness (Schuh et al, 2017).…”
Section: The Effect Of a Mindfulness Intervention On Followers' Job Amentioning
confidence: 99%